Determinan Niat Aparatur Daerah untuk Melakukan Whistleblowing pada Konteks Fraud - Mardah, Mardah; Supri, Zikra; Sari, Nispa (E-Jurnal Akuntansi, 2021)
This study aims to analyze organizational commitment, level of seriousness of fraud, and personal costs on the intention of whistleblowing fraud by the local apparatus of Palopo City. Sampling using purposive sampling technique. A total of 120 respondents were used as research samples. The sample is local officials who work at the PUPR and BPKAD offices. The data analysis technique was carried out using multiple linear regression analysis method with SPSS V.22 application. The results of the study indicate that the seriousness of fraud affects the whistleblowing intention of the regional apparatus of Palopo City. Meanwhile, organizational commitment and personal costs have no effect on the intention of whistleblowing fraud by the Palopo City apparatus. Keywords :  Organizational Commitment; Fraud Seriousness Level; Personal Costs; Intention of Whistleblowing Fraud.